Controls on high and low groundwater arsenic on the opposite banks of the lower reaches of River Ganges, Bengal basin, India - Mukherjee, Abhijit; Fryar, A.; Eastridge, E.; Nally, R.; Chakraborty, M.; Scanlon, B. (Elsevier, 2018)
Understanding the controls on spatial variability of groundwater arsenic (As) is critical for mitigating As contamination. The objective of this study is to determine controls on previously unexplained differences in groundwater As concentrations, which are high along the east bank and low along the west bank of the River Bhagirathi-Hoogly (B-H), the primary Indian distributary of the River Ganges, on the western margin of the Bengal basin. A total of 54 wells were sampled after the monsoon season at four sites (two each east and west of the B-H) in Murshidabad district, West Bengal, for field parameters, major and minor solutes, and stable isotopes of water. An additional four boreholes were drilled for analyses of sediment texture, mineralogy, total organic and inorganic carbon, and total As and other metal(loid)s. Results show that higher As in east-bank groundwater (median 0.031 mg/L) is associated with generally more anoxic conditions (higher median total Fe and lower median EHand NO3-) relative to west-bank groundwater (median As < 0.001 mg/L), consistent with previous studies. In contrast, concentrations of Mn in the study area are highest in west-bank wells near the B-H. Carbonate and silicate weathering appear to be more important in east- and west-bank groundwater, respectively, which may reflect differences in sediment sources. Ranges of total As are similar in east- and west-bank sediments. Relatively depleted values of d18O and d2H in the east-bank aquifer and streams appear to reflect focused recharge through paleochannels, while relatively enriched west-bank values suggest diffuse recharge to upland aquifers. We speculate that water infiltrating through erosional, stratigraphic “windows” carries organic matter capable of mobilizing As in east-bank groundwater. This comprehensive evaluation of groundwater chemistry provides a more detailed understanding of controls on As variability within the basin.